Perifiton Sebagai Bioindikator di Perairan Kawasan Pulau Pedalaman Kabupaten Mempawah, Kalimantan Barat: Perifiton Sebagai Bioindikator di Perairan Kawasan Pulau Pedalaman Kabupaten Mempawah, Kalimantan Barat - Apriyanti; Padmarsari, Widadi; Hurriyani, Yeni; Hadinata, Fitra Wira (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2023)
Pulau Pedalaman Mempawah Regency is a potential public water area in the form of small lakes and protected forests. Has an important role in the life of microorganisms in waters, but is vulnerable to environmental changes and pollution caused by human activities. This study aims to determine the community structure and saprobity index as well as to determine the condition of the waters based on periphyton in the waters of the Inland Island Region of Mempawah Regency. Sampling and water quality measurements were carried out for 3 months, from September to November 2021 at five research stations. The results showed that 44 genera were identified as belonging to 4 classes, namely Bacillaiophyta, Chlorophyta, Cyanophyta and Euglenophyta. The highest relative abundance of periphyton was Bacillariophyta (84.70%). Followed by Chlorophyta (14.90%), Cyanophyta (0.17%) and Euglenophyta (0.22%). Overall diversity indices from all sampling locations showed high diversity or tended to have fairly stable waters. The saprobity index value was in the light to very light pollution level which was in the Meso/Oligosaprobic and Oligo/mesosaprobic phases.